Wing strain installation disk [compact disc] - 441514 Lee, Chi Wei (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Engineering (Mechanical)) - Universiti Teknologi Malaysia, 2001